Beyond the standard quantum limit for parametric amplification of broadband signals - M. Renger; S. Pogorzalek; Q. Chen; Y. Nojiri; K. Inomata; Y. Nakamura; M. Partanen; A. Marx; R. Gross; F. Deppe; K. G. Fedorov (npj Quantum Information, 2021)
Abstract The low-noise amplification of weak microwave signals is crucial for countless protocols in quantum information processing. Quantum mechanics sets an ultimate lower limit of half a photon to the added input noise for phase-preserving amplification of narrowband signals, also known as the standard quantum limit (SQL). This limit, which is equivalent to a maximum quantum efficiency of 0.5, can be overcome by employing nondegenerate parametric amplification of broadband signals. We show that, in principle, a maximum quantum efficiency of unity can be reached. Experimentally, we find a quantum efficiency of 0.69 ± 0.02, well beyond the SQL, by employing a flux-driven Josephson parametric amplifier and broadband thermal signals. We expect that our results allow for fundamental improvements in the detection of ultraweak microwave signals.